(3cJGH EfTGA HGdJQcjIs
(3ChdgG (B:s
(3gPG cJGH EfTGA hRjQ CYXe s
(3BNQgG (B:s
(3Ke HYhf Gddg GdYRjR GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HChdgG hbajI HGSe edG YHO Gddg GdYHOdi Ydi ChdGOg hjQLY JGQjNgG Edi SfI (B1239 (3g`s
(3HgG fXGe GdJYbjHIs
(3GdcJGH HGddZg GdJQcjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs